Utilização dos cadernos digitais para o ensino de lógica de programação - Fernandes, Mayara Leal Reis (2023)
Information and Communication Technologies (ICT) are being investigated as innovative ways of supporting the teaching and learning processes in schools, universities, and training programs. In computer science courses, the Programming Logic subject is considered a fundamental requirement. However, the low performance of students in this subject compromises their educational journey and becomes a barrier to their learning. In this context, technological tools, especially digital notebooks and virtual documents that allow the inclusion of multimedia content and the execution of written code simultaneously, using Jupyter Notebook, have stood out as important digital technologies in the field of education. Given this situation, this research aimed to evaluate how the use of digital notebooks in Programming Logic, guided by a didactic sequence, can contribute to the teaching and learning processes for students in technical courses. This research adopts a qualitative and applied approach. Its objectives are exploratory in nature. The technical procedures employed categorize this investigation as a case study. Data collection methods include observations, photo records, field diaries, and questionnaires. The study involved first-year students in the Computer Networks technical course integrated to high school at the Instituto Federal de Educação, Ciência, e Tecnologia do Maranhão - Campus São João dos Patos, through practical workshop organized into four sessions, with one weekly meeting lasting 3 hours each, conducted over three weeks, and, lastly, a product evaluation questionnaire was distributed via email to the research participants. For the development of the practical workshop, a didactic sequence was developed as the final product, utilizing digital notebooks in the teaching and learning process of sequential structure and decision structures of the Programming Logic curriculum component. With the analysis of the results, it is concluded that the didactic sequence is adequate for the purposes of the research, the use of Jupyter Notebook was found to be satisfactory in the educational process, serving as a valuable facilitator in promoting dynamic and interactive learning, in which majority of students agreed that the use of digital notebooks contributed to a dynamic class environment and motivated them to learn Programming Logic.